Long‐Term Characteristics of the Meteor Radar Winds Observed at King Sejong Station, Antarctica. Issue 1 (28th December 2022) - Song, B.‐G.; Chun, H.‐Y.; Song, I.‐S.; Lee, C.; Kim, J.‐H.; Jee, G.
Abstract: The characteristics of the horizontal wind in the mesosphere and lower thermosphere (MLT) at King Sejong Station (KSS) in the Antarctic Peninsula are investigated using approximately 15‐year (March 2007–November 2021) meteor radar (MR) observations. The 15‐year climatology and variability of the MLT winds at KSS are analyzed for the first time, and comparisons with the observations at other Antarctic stations are performed. The short‐period oscillations (periods between 2 hr and 10 days) of the winds, including tides and several planetary wave components, are examined for each month. Temporal and altitudinal variations in the amplitudes of the semidiurnal and diurnal tides, the two largest short‐period components, are analyzed. Annual and semiannual oscillations of the wind are distinct below and above z  = 90 km, respectively. The long‐term trend of the zonal wind is estimated through a multiple linear regression analysis. Statistically significant trends of the zonal wind of ∼0.5–0.8 m s −1  yr −1 appear above z  = 90 km in July. To understand observed MLT wind trends, the gravity‐wave momentum flux and gravity‐wave drag (GWD) in the MLT region are estimated from the MR observations at KSS for the 15 years. Similar seasonal variations are found between the trends of the zonal winds and zonal GWDs, especially above z  = 94 km. In July where a strong positive zonal wind trend appears, positive correlation between the zonal wind and zonal GWDs is found to be statistically significant above z  = 94 km. Plain Language Summary: The mesosphere and lower thermosphere (MLT) is the atmospheric layer between the Earth's lower atmosphere and space. A meteor radar (MR) can be used to observe the horizontal winds in the MLT region. In this study, we analyze the characteristics of the MLT winds using the recent 15‐year MR observations at King Sejong Station (KSS; 62.22°S, 58.78°W) located in the Antarctic Peninsula. We find that the zonal and meridional components of the MLT wind at KSS exhibit temporal variability on various timescales. Statistically significant trends of the zonal wind appear above z  = 90 km in July. To understand the observed MLT wind trends, we calculated the gravity‐wave momentum flux and gravity‐wave drag (GWD) using the MR observations at KSS for 15 years, which are quite unique data for such a long time period. A similar seasonal pattern between the zonal wind and the zonal GWD suggests that the positive zonal wind trend observed from the MR at KSS in July is likely related to that of the GWD. Key Points: Horizontal winds in the mesosphere and lower thermosphere at King Sejong Station are investigated using 15‐year meteor radar observations The 15‐year climatology, short‐ and long‐period variability, and long‐term trends of the observed winds are examined Significant positive zonal wind trends above 90 km are, to a certain degree, associated with zonal gravity wave drag trends